Prediction of major intravascular hemolysis during pulsed electric field ablation of atrial fibrillation using a pentaspline catheter - Stojadinović, Predrag; Ventrella, Nicoletta; Alfredová, Hana; Wichterle, Dan; Peichl, Petr; Čihák, Robert; Ing, Vanda Filová; Borišincová, Eva; Štiavnický, Petr; Hašková, Jana; Franeková, Janka; Kautzner, Josef (Journal of cardiovascular electrophysiology, 2024)
INTRODUCTION: Pulsed electric field (PEF) has emerged as a promising energy source for catheter ablation of atrial fibrillation (AF). However, data regarding the in-vivo effect of PEF energy on erythrocytes during AF ablation procedures are scarce. This study aimed to quantify the impact of PEF energy on erythrocyte damage during AF ablation by assessing specific hemolytic biomarkers. METHODS: A total of 60 patients (age: 68 years, males: 72%, serum creatinine: 91 μmol/L) with AF underwent catheter ablation of AF using PEF energy delivered by a multipolar pentaspline Farawave catheter (Farapulse, Boston Scientific, Inc.). Ablation beyond pulmonary vein isolation was performed at the operator's discretion. Peripheral venous blood was sampled for assessing the plasma levels of free hemoglobin (fHb), direct (conjugated) bilirubin, lactate dehydrogenase (LDH), and creatinine before, immediately after the ablation, and on the next day. RESULTS: Following the PEF ablation with duration of [median (interquartile range)] 75 (58, 95) min, with 74 (52, 92) applications and PVI only in 27% of patients, fHb, LDH, and direct bilirubin significantly increased, from 40 (18, 65) to 493 (327, 848) mg/L, from 3.1 (2.6, 3.6) to 6.8 (5.0, 7.9) μkat/L, and from 12 (9, 17) to 28 (16, 44) μmol/L, respectively (all p < .0001). A strong linear correlation was found between the peak fHb and the number of PEF applications (R = 0.81, p < .001). The major hemolysis (defined as fHb >500 mg/L) was predicted by the number of PEF applications with the corresponding area under the receiver operating characteristic curve of 0.934. The optimum cut-off value of >74 PEF applications predicted the major hemolysis with 89% sensitivity and 87% specificity. CONCLUSION: Catheter ablation of AF using PEF energy delivered from a pentaspline catheter is associated with significant intravascular hemolysis. More than 74 PEF applications frequently resulted in major hemolysis. However, the critical amount of PEF energy that may cause kidney injury in susceptible patients remains to be investigated.
Keywords: výsledek terapie; L-laktátdehydrogenasa; hemolýza; Hemolysis; Hemoglobins; Male; biologické markery; Risk Factors; Biomarkers; Equipment Design; Creatinine; Bilirubin; Aged; bilirubin; mužské pohlaví; senioři; hemoglobiny; Catheter Ablation; Predictive Value of Tests; design vybavení; Atrial Fibrillation; Treatment Outcome; Time Factors; lidé; Cardiac Catheters; ženské pohlaví; Humans; časové faktory; rizikové faktory; kreatinin; erytrocyty; prediktivní hodnota testů; Erythrocytes; L-Lactate Dehydrogenase; katetrizační ablace; Female; lidé středního věku; srdeční katétry; fibrilace síní; Middle Aged